UPAYA PEMERINTAH INDONESIA DALAM MENINGKATKAN EKSPOR GARMEN KE AMERIKA SERIKAT (2012-2015) - Tiah Rifkah Dina Syafitri; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the Government Efforts in Increasing Garment Exports to the United States on 2012-2015. Garment sector industry plays an important role in the Indonesian economy as a foreign exchange and create jobs. Indonesia has been recognized by the world as a producing country of Textile and Textile Products. But much of the competition makes the Indonesian garment industry to make efforts to improve.The method used in this research is qualitative. The data obtained comes from books, journals, theses, articles, internet sites and other sources related to research. The focus of this research is how the Indonesian government attempts to increase garment exports to the United States. This research uses the perspective of liberalism, the theory of international trade and comparative advantage.The efforts have been made by the Indonesian government in increasing garment exports to the United States are divided into two areas, namely external and internal. External effort is to enter into a cooperation agreement in trade in textile and apparel goods. And internal is by improving human resources, providing supportive policies such as income tax reduction, subsidizing sewing machine tools, restricting imports, and expanding international promotions and exhibition.Key words :Garment, Textile, Neoliberalism,export